“That’s your patient. There’s your ventilator”: exploring induction to work experiences in a group of non-UK EEA trained anaesthetists in a London hospital: a qualitative study - Snelgrove, Huon (BMC Med Educ, 2015)
BACKGROUND: European health systems depend increasingly on the services of health professionals who obtained their primary medical qualification from other countries. There has been a significant increase recently in fully qualified specialist doctors arriving from the European Union to provide short term or longer-term solutions to health human resources needs in the UK National Health System. These doctors often take up senior consultant positions. As a result, the NHS has had to learn to deal with both expatriation and repatriation of EU doctors as a constant dynamic characteristic of its own ability to deliver services. We conducted a qualitative study to explore the acclimatisation experience of EU doctors with qualifications in anaesthesia arriving in the United Kingdom to take up clinical employment in the NHS. The question we ask is: how do specialty registered anaesthetists who trained in other European countries experience the process of acclimatisation to practice in the United Kingdom in a large hospital in London? METHODS: We did individual interviews with non-UK, EU-qualified doctors with Certification of Completion of specialty Training who were registered with the General Medical Council in the UK and could practice in the NHS as specialist anaesthetists. The doctors were all interviewed whilst working in a large NHS teaching hospital in London, UK. We analysed qualitative data from interview transcripts to identity themes and patterns regarding senior doctor’s acclimatisation to the British system. RESULTS: Acclimatisation conceived of as transfer of clinical expertise was problematic for doctors who felt they lacked the right kind of support. Doctors sought different opportunities to share wider perspectives on care deriving from their previous experience. CONCLUSIONS: Hospital conceptions of acclimatisation as a highly individual process can offer an idealized view of clinical work and learning in the new system. Socio-cultural theories suggest we create regular learning opportunities for international staff to critically reflect on practice with local staff to acclimatise more effectively. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-015-0331-4) contains supplementary material, which is available to authorized users.